A territorialização do agronegócio canavieiro em Frutal - MG - Souza, Andreza Gomes de (2012)
The reaffirmation of sugar-energy sector importance nowadays occurs in the middle of a dual crisis of: energy and climate. In order to solve them and also as a solution for the future, agroenergy production has been adopted. However, what is implicit in the expansion of sugarcane agro-fuel limits converges into the productive restructuring of capital. In this research, we aim to understand how sugarcane agribusiness process of territorialization has happened in the city Frutal, highlighting the reasons that transformed the city so attractive to such investments, such as sugarcane mills Frutal (Bunge) and Cerradão. To do so, we rely on bibliographic material and internet, on interviews and data analysis compilation to sustain our research. We have elected to study Frutal (Bunge group) sugarcane plant and Cerradão (Queiroz de Queiroz and Pitangueiras group), institutions like Sindicato dos Trabalhadores Rurais de Frutal and Sindicato Rural (employers), Associação dos Produtores de Cana do Vale do Rio Grande (APROVALE) and local public authorities. Sugarcane agribusiness territorialisation in Frutal and in the middle region of Triângulo Mineiro/Alto Paranaíba embodies brazilian s choice for sugarcane agro-fuel, which consists of an alternative to solve crises, specially the capital one. During this process, we have realized that changes on work environment, such as insertion of more technology into sugarcane production steps, demand for qualified workforce, the adoption of sustainable practices inside sugar mills are strategies to ensure agroindustryes image promotion and their presence on internal and international market. Optimistic projections concerning agro-fuel were smoothed by worldwide financial crisis outbreak which has reflected on sugar-energy sector, as noted by the greater participation of foreign capital into this area. In this context of foreign determinations associated with the obligation to pay debts, Moema group, from São Paulo, had to negotiate the sale of its sugar mills to multinational Bunge. If the projections of sugar-energy sector reheating become true, there will be more demand for land and, therefore, its appreciation, what might achieve traditional crops areas. Also, the same spot that can be used to soybean plantation or livestock can be changed according to convenience and the demands of the production methods at the time, becoming sugarcane territory, once limits are established, as well as a demand for services and qualified workforce, and the possession of lands either by property rental or the sale.